J. F. WILLUMSENS „GAMLE SAMLING“: Vurderingens omskiftelighed og samlerens strategier - Rasmussen, Mikael Bøgh (Tidsskriftet Antropologi, 2001)
From his early years until his death, the Danish multi-talented artist, Jens Ferdinand Willumsen (1863-1958), amassed a large private collection of art and artifacts of all kinds. Emulating his famous 19th century predecessor, Bertel Thorvaldsen, Willumsen bequeathed his collection in 1947 to the Danish state together with a large portion of his own substantial artistic production. On that occasion he arranged a double exhibition to show his own works and the so-called “Old Collection”. The article deals with the reception of the “Old Collection” and the very severe critique that it met for its supposed lack of quality. The article describes the reactions and the subsequent changes in attitude towards the collection. Today the collection is recognized as one that includes many important works of art. The second part of the article is an attempt to identify some of J. F. Willumsen’s reasons for collecting: The artist collected things which could inspire him. He tried with his collection to create the impression of himself as a particularly gifted “uomo universale” who, through his artistic intuition, would find a way to the old masters that was unknown to the learned art historians. The “Old Collection” was thus a means of displaying his – not always acknowledged – genius. Finally, its seems that the com-bination of his own workshop-collection with an art collection, installed together in a museum dedicated to him alone, was a way of linking himself with Thorvaldsen, who was during the Golden Age of Danish painting the only other Danish artist who had a museum of his own, comprising both his own works and his collection of other masterworks.